KITENIN promotes aerobic glycolysis through PKM2 induction by upregulating the c-Myc/hnRNPs axis in colorectal cancer - Mücahit Varlı; Sung Jin Kim; Myung-Giun Noh; Yoon Gyoon Kim; Hyung-Ho Ha; Kyung Keun Kim; Hangun Kim (Cell & Bioscience, 2023)
Abstract Purpose The oncoprotein KAI1 C-terminal interacting tetraspanin (KITENIN; vang-like 1) promotes cell metastasis, invasion, and angiogenesis, resulting in shorter survival times in cancer patients. Here, we aimed to determine the effects of KITENIN on the energy metabolism of human colorectal cancer cells. Experimental design The effects of KITENIN on energy metabolism were evaluated using in vitro assays. The GEPIA web tool was used to extrapolate the clinical relevance of KITENIN in cancer cell metabolism. The bioavailability and effect of the disintegrator of KITENIN complex compounds were evaluated by LC–MS, in vivo animal assay. Results KITENIN markedly upregulated the glycolytic proton efflux rate and aerobic glycolysis by increasing the expression of GLUT1, HK2, PKM2, and LDHA. β-catenin, CD44, CyclinD1 and HIF-1A, including c-Myc, were upregulated by KITENIN expression. In addition, KITENIN promoted nuclear PKM2 and PKM2-induced transactivation, which in turn, increased the expression of downstream mediators. This was found to be mediated through an effect of c-Myc on the transcription of hnRNP isoforms and a switch to the M2 isoform of pyruvate kinase, which increased aerobic glycolysis. The disintegration of KITENIN complex by silencing the KITENIN or MYO1D downregulated aerobic glycolysis. The disintegrator of KITENIN complex compound DKC1125 and its optimized form, DKC-C14S, exhibited the inhibition activity of KITENIN-mediated aerobic glycolysis in vitro and in vivo. Conclusions The oncoprotein KITENIN induces PKM2-mediated aerobic glycolysis by upregulating the c-Myc/hnRNPs axis.